Multiscale thermal-hydraulic modeling of the pebble bed fluoride-salt-cooled high-temperature reactor. (May 2021) - Novak, A.J.; Schunert, S.; Carlsen, R.W.; Balestra, P.; Slaybaugh, R.N.; Martineau, R.C.
Highlights: Pronghorn's multiscale thermal-hydraulic models are applied to the Pebble Bed. Fluoride-Salt-Cooled High-Temperature Reactor (PB-FHR). The Heat Source Decomposition method is compared against fully-resolved pebble heat conduction. Anisotropic drag models are correlated with COMSOL for the outer reflector blocks. Predictions are made for the bypass fraction and core thermal-hydraulic characteristics at nominal steady-state conditions. Abstract: The complex core geometry of Pebble Bed Reactors (PBRs) necessitates multiscale techniques for fast-turnaround design and analysis. This paper describes the multiscale model implemented in the Pronghorn PBR simulation tool and demonstrates application to steady-state analysis of the Mark-1 Pebble Bed Fluoride-Salt-Cooled High-Temperature Reactor (PB-FHR). Verification of the pebble model with fully-resolved heat conduction shows that material-wise pebble temperatures are predicted to within 10°C over a wide range in thermal conditions. Anisotropic drag models are correlated for the outer reflector blocks using COMSOL, providing closures for modeling of bypass flows. With a porous media model of the outer reflectors, the core bypass fraction and fuel, reflector, and structural material temperatures are predicted for a number of different inflow conditions. This work demonstrates the full-core analysis capabilities of the Pronghorn application and enables comprehensive reactor analysis with the Multiphysics Object-Oriented Simulation Environment (MOOSE) framework.